Neurofibromatosis: chronological history and current issues Neurofibromatose: histórico cronológico e aspectos atuais - João Roberto Antônio; Eny Maria Goloni-Bertollo; Lívia Arroyo Trídico (Sociedade Brasileira de Dermatologia, 2013)
Neurofibromatosis, which was first described in 1882 by Von Recklinghausen, is a genetic disease characterized by a neuroectodermal abnormality and by clinical manifestations of systemic and progressive involvement which mainly affect the skin, nervous system, bones, eyes and possibly other organs. The disease may manifest in several ways and it can vary from individual to individual. Given the wealth of information about neurofibromatosis, we attempted to present this information in different ways. In the first part of this work, we present a chronological history, which describes the evolution of the disease since the early publications about the disorder until the conclusion of this work, focusing on relevant aspects which can be used by those wishing to investigate this disease. In the second part, we present an update on the various aspects that constitute this disease. A neurofibromatose, descrita inicialmente em 1882 por Von Recklinghausen, é uma doença genética caracterizada por uma anormalidade neuroectodérmica e por manifestações clínicas de envolvimento sistêmico e progressivo, que acometem principalmente a pele, o sistema nervoso, ossos, olhos e eventualmente outros órgãos, podendo apresentar uma grande diversidade de manifestações que variam de indivíduo para indivíduo. Diante da riqueza de informações encontradas a respeito da neurofibromatose, buscamos apresentá-la sob diversos aspectos, organizando os conhecimentos a respeito dessa doença. Na primeira parte desse trabalho, apresentamos um histórico cronológico, relatando a evolução dessa doença desde os primórdios das publicações a ela referentes até o momento do término desse trabalho, dando ênfase aos fatos relevantes ao seu conhecimento e que possam ser utilizados por aqueles que pretendam pesquisar a respeito dessa afecção. Na segunda parte, apresentamos uma atualização sobre os diversos aspectos que compõem essa doença.